Crop Level and Harvest Date Impact on Four Ontario Wine Grape Cultivars. II. Wine Aroma Compounds and Sensory Analysis - Morena Luna, L.H.; Reynolds, A.G.; di Profio, F.A.; Zhang, L.; Kotsaki, E. (South African Journal of Enology and Viticulture, 2018)
Pinot gris, Riesling, Cabernet franc and Cabernet Sauvignon from a vineyard in Virgil, Ontario, Canada were subjected by cluster thinning to two crop-level treatments (full crop, half crop), combined with three harvest dates (commercial harvest (T0), three weeks after T0 (T1), six weeks after T0 (T2)) in a randomised experiment in 2011 and 2012, with wines produced from all treatment replicates. We hypothesised that a full crop with substantially delayed harvest date might have a greater impact on wine aroma than reducing crop level. Wine aroma volatile analysis was carried out by GC-MS, with quantification by calibration with analytical standards prepared in model wine. Delayed harvest overcame the effects of crop reduction for almost all volatiles. Pinot gris and Riesling displayed increases in varietal aromas in the T1 and T2 wines, e.g. monoterpenes and norisoprenoids, and in esters, aldehydes and alcohols. Reduced concentrations of volatile acids and green odour compounds (e.g. 1-hexanol) with delayed harvest were also evident. Increases in ethanol were related to increased berry sugars, but higher alcohols did not necessarily increase with harvest date. Crop level had little impact on the sensory properties of these cultivars in both seasons. However, delayed harvest resulted in substantial sensorial changes. Due to these chemical and sensorial effects, delayed harvest is recommended, rather than crop-level reduction, to enhance wine quality in these cultivars. Extended harvest, e.g. T2 treatments, was associated with the production of benzaldehyde, diethyl acetal, and higher concentrations of higher alcohols, e.g. isoamyl alcohol and nonanol, which could be linked to pre-harvest desiccation.